Distribution of leaf dissection and sclerophylly along microhabitat gradients in pteridophytes of the Cape peninsula - Viljoen, Jan-Adriaan (Department of Biological Sciences, 2017)
Plant species with small leaves and sclerophylls have been reported to occur mainly on dry, low-nutrient soils in situations of high insolation. However; a number of physiological functions have been proposed for the two sets of traits. Ferns are well-suited to the study of leaf structure and its impact in different environments, as they show remarkable variation in leaf dissectedness and sclerophylly, and are able to inhabit a variety of marginal habitats. In this study, ecological and leaf trait data were collected for 17 fern species occurring in Skeleton Gorge, Table Mountain, in the Western Cape. Correlations between the traits and regressions of leaf traits on potential environmental determinants was carried out using both species averages and phylogenetically independent contrasts. The habitat and leaf traits were also subjected to a test of evolutionary trait conservatism. Sclerophyllous plants were found to be have thicker leaves, containing less chlorophyll, but sclerophylly was poorly correlated with leaf dissection. Plants occurring in high-light environments tended to be more sclerophyllous and have more dissected leaves, although these environments also were nutrient-poor. Leaf dissection appears to be primarily a means of dissipating heat by convection, rather than evaporative cooling, but it may also improve nutrient acquisition in low-nutrient soils. Sclerophylly in these ferns was not directly associated with nutrients; instead low sclerophylly seems to be favoured in low-light environments, perhaps because of lower metabolic costs or to reduce self-shading.